BODIES AND SIMULACRA: STRIP ENACTMENTS ON THE INTERNET - Silva, Weslei Lopes (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2016)
This text is originated from an ethnography that aimed to analyze how a group of women deals with the experience of working in the virtual strip-tease market and how they sense the body in interactions with the customers via the Internet. From the notions of incorporation, of gender performance and simulacrum, I seek to reflect on how they build themselves as web strippers from their body, which requires the consecutive modification of it, to always be appropriate to the “commodity situation’’. In this meaning, they seek to meet the aesthetic standards seen as suitable to their occupation and add innovations to the strip-tease market, which refer mainly in taking new body provisions, different practices and incorporating new characters. Furthermore, the erotic scenes built by the web strippers from the inventive use of body constitute female performance that temporarily demand the dismissal of themselves and the composition of another woman (or other women) to the shows. Overall I try to show the lines, the experiences, the interrelations and the daily work life of these women in order to acknowledge and comprehend their role in the sex market, and the way that each one of them, in their own values, see and give meaning to reality.